What should be considered if you decide to build your own mathematical model for predicting the development of bacterial resistance? Recommendations based on a systematic review of the literature - Arepeva, Maria; Kolbin, Alexey; Kurylev, Alexey; Balykina, Julia; Sidorenko, Sergey (Frontiers in Microbiology, 2015)
Acquired bacterial resistance is one of the causes of mortality and morbidity from infectious diseases. Mathematical modeling allows us to predict the spread of resistance and to some extent to control its dynamics. The purpose of this review was to examine existing mathematical models in order to understand pros and cons of currently used approaches and to build our own model. During the analysis, seven articles about the mathematical approaches to studying resistance that satisfied the inclusion / exclusion criteria were selected. All models were classified according to the approach used to study resistance in the presence of antibiotic and were analyzed in terms of our research. Some models require modifications associated with the specific of the research. Further work plan of model building is as follows: modify some models, according to our research, check all obtained models on our data, and select the optimal model or several models with the best quality of prediction. After that we would be able to build a model for the development of resistance using the obtained results.